Association Between Dysmenorrhea and Endometrial Cancer: A Mendelian Randomization Study - Qiuyuan Huang; Xizhen Huang; Liyuan Huang; Yanglin Wang; Suyu Li; Xiangqin Zheng (Pain Research and Management)
Conclusion: This study indicates a potential inverse relationship between dysmenorrhea and EC risk. These findings provide novel causal evidence for understanding complex associations in female reproductive health, underscoring the need for further research on dysmenorrhea in EC prevention.